ANALISIS PENGUKURAN DAN PENILAIAN KUALITAS PENERIMAAN SIARAN RADIO FM MENGGUNAKAN FIELD STRENGTH PADA DAERAH SUB URBAN KABUPATEN SANGGAU - ., M.Riski Pratama (Jurnal Teknik Elektro Universitas Tanjungpura, 2019)
Radio Broadcast FM is one of the technology telecommunications used for give away service information and entertainment for society. For reach society listener as targeted consumers, quality reception broadcast to be the very thing crucial . Power emit and propagation from transmitter could influence technical quality service on the recipient. Problem quality this to be the object under study and the approach taken for get results, carried out measurement field with use field strength instruments and plus GPS as determinant accuracy location measurement. Use spectrum radio frequency must corresponding with legislative decisions by Ministry Transportation and not each other disturbing. Use illegal radio frequency could make occurrence disorder that can bring down quality from other radio stations, and harm for station which is on official to be legal user. If seen from results measurement quality reception radio broadcasts in the District Sub- District area Sanggau who use SINPO approach ( Signal, Interference, Noise, Propagation , Overall ), still many area around the border that is experiencing interference, in the form of "spillover / spill" radio broadcast from countries neighbors, especially Hamlet Silup, Hamlet Bodok on frequency 97.00 MHz (I) Broadcast Radio FM Indonesia, Jl. Raya Bodok on frequency of 106.00 MHz (I) Broadcast Radio FM Indonesia, Hamlet Parindu on frequency 106.00 (I) Broadcast Radio FM Indonesia, Simpang Tanjung on frequency 107.40 (I) Broadcast Radio FM Indonesia, Hamlet Bunut on frequency of 107.60 MHz (I) Broadcast Radio FM Indonesia, Hamlet Kembayan on frequency 104.20 MHz (I) RRI PRO 1 Pontianak, Hamlet Kenaman on frequency of 96.70 MHz (I) Sonora FM, Hamlet Beduai on frequency of 96.70 MHZ (I) Sonora FM, Hamlet Beduai on frequency of 100.70 MHz (I) RRI Entikong, Dusun Tanjung Munying on frequency of 100.70 MHz (I) RRI Entikong, Dusun Kembayan on frequency of 100.70 MHz (I) RRI Entikong, Dusun Kembayan on frequency of 106.00 MHz (I) Broadcast Radio FM Indonesia, Hamlet Parindu on frequency 106.00 MHz (I) Indonesian FM Radio Broadcasting, Hamlet Parindu on frequency of 86.90 MHz (I) Broadcast Radio FM Indonesia, Hamlet Bodok on frequency of 106.00 MHz (I) Broadcast Radio FM Indonesia, Jl.Raya Bodok on frequency of 106.00 MHz (I) Indonesian FM Radio Broadcast, Sanggau City on frequency of 106.00 MHz (I) Indonesian FM Radio Broadcasts. Disorders spectrum radio frequency is disturbance consequence energy that doesn't resulting desired by one or combination emissions, radiation or induction-induction to reception in system radio communication indicated with existence something decline quality .